2020
DOI: 10.13057/biodiv/d210510
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of entomopathogenic fungal culture filtrate of lowland and highland soil of South Sumatra (Indonesia) against Spodoptera litura larvae

Abstract: Abstract. Gustianingtyas M, Herlinda S, Suwandi, Suparman, Hamidson H, Hasbi, Setiawan A, Verawaty M, Elfita, Arsi. 2020. Toxicity of entomopathogenic fungal culture filtrate of lowland and highland soil of South Sumatra against Spodoptera litura larvae. Biodiversitas 21: 1839-1849. The use of secondary fungal metabolites for the active ingredient of mycoinsecticide is more effective and more easily integrated with other pest control techniques. This study aimed to measure the toxicity of the culture filtrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Color change in the samples indicated that secondary metabolite compounds had been formed. As a comparison, 300ml of the PDB medium was placed into a separate 1L bottle along with secondary metabolites, which had been partitioned in ethyl acetate and extracted via evaporation (Elfita et al 2019;Gustianingtyas et al 2020). The concentrated extracts were used for antimicrobial assay.…”
Section: Cultivation and Extractionmentioning
confidence: 99%
“…Color change in the samples indicated that secondary metabolite compounds had been formed. As a comparison, 300ml of the PDB medium was placed into a separate 1L bottle along with secondary metabolites, which had been partitioned in ethyl acetate and extracted via evaporation (Elfita et al 2019;Gustianingtyas et al 2020). The concentrated extracts were used for antimicrobial assay.…”
Section: Cultivation and Extractionmentioning
confidence: 99%
“…The larvae that were infected and death caused by the fungi in this study showed the symptoms of his body got dried, shriveled, smaller, and odorless, while the integument was covered by mycelia and conidia resembling yellowish-white flour mixed with dark green similar to the symptoms described by Thaochan and Sausa-Ard (Thaochan and Sausa-Ard 2017). The symptoms of the infected insects due to the entomopathogenic fungal infections vary depending on favorable environmental conditions, for example, relative humidity higher than 62% (Gutiérrez-Cárdenas et al 2019), then the mycelia and mature conidia can grow well and cover the entire body of the insect, and the condition of unfavorable mycelia and conidia does not appear (El-Ghany 2015). Metarhizium had been reported to be effective against Aphis craccivora (Mweke et al 2019), Spodoptera litura (Gustianingtyas et al 2020), and Sitophilus oryzae (Kavallieratos et al 2015).…”
Section: Isolatesmentioning
confidence: 99%
“…The soil which is a fungal habitat during the saprophytic phase has high entomopathogenic fungi inoculum potential, especially those close to plant roots (Safitri et al 2018) and is effective in killing the insect pests (Ayudya et al 2019;Sumikarsih et al 2019;Gustianingtyas et al 2020). Research results from other countries show the high pathogenicity of entomopathogenic fungi from soil in controlling S. frugiperda population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entomopathogenic fungi such as Beauveria bassiana (Ascomycota: Hypocreales) and Metarhizium anisopliae (Ascomycota: Hypocreales) are the most commonly used bioinsecticides (Prabawati et al 2019). B. bassiana and M. anisopliae are widely used because they are easily found in freshwater swamps (Herlinda et al 2018b;Safitri et al 2018;Gustianingtyas et al 2020). and able to kill important insect pests such as brown planthopper, Nilaparvata lugens (Homoptera: Delphacidae) (Sumikarsih et al 2019) and Spodoptera litura (Lepidoptera: Noctuidae) (Ayudya et al 2019).…”
Section: Introductionmentioning
confidence: 99%